PENATAAN POTENSI KAWASAN WISATA BAHARI DI DESA OLELE - Hasanah, Luluk Lailatul; Eka, Rahmawati (Universitas Bina Taruna Gorontalo, 2023)
Olele is one of the villages in the Sulawesi archipelago with excellent potential as a tourist spot. The village, which is located in Gorontalo, is nicknamed